The tadpoles and advertisement calls of Pleurodema bibroni Tschudi and Pleurodema kriegi (Müller), with notes on their geographic distribution and conservation status (Amphibia, Anura, Leiuperidae) - Kolenc, Francisco; Borteiro, Claudio; Baldo, Diego; Ferraro, Daiana P.; Prigioni, Carlos (Zootaxa, 2009)
Pleurodema bibroni and P. kriegi are poorly known species with a troublesome taxonomic history. They are cryptic taxa, currently considered as valid species on the grounds of biogeographic and ecological differences. The first is known from much of southern Uruguay and from the northeastern region of the State of Rio Grande do Sul, Brazil (from sea level to 900 m a.s.l.); the latter is restricted to high grasslands of the Sierras Grandes in central Argentina, between 800–2000 m a.s.l. Herein, we compare their tadpoles and advertisement call and provide some notes on their conservation status and natural history. The tadpoles of both species are very similar, belonging to the benthic ecomorphological guild, and are characterized by: total length about 35 mm at stages 33–36; globose body; short lateral sinister spiracle posterodorsally directed; pineal end organ visible between the eyes; medial vent tube, with its opening aligned with the ventral fin, directed to the left or to the right; vent tube enclosed in a transparent saccular structure underlying the limb buds; tail length about 60% of the total length, with bluntly rounded tip; oral disc anteroventral, laterally emarginated, with very robust jaw sheaths and marginal papillae arranged in a single or double row with a large dorsal gap; labial tooth row formula 2(2)/3(1); gap in A2 wide with the upper jaw sheath partially placed within it; P3 about half the length of the other rows. The advertisement call exhibits the same temporal and spectral structure in both species. It consists of long trills (up to about 45–70 s) that are emitted sporadically; notes are about 0.044–0.062 s, separated by gaps of 0.024–0.058 s (note repetition rate 8.9–13.2/s) and have three pulses. Dominant frequency ranges between 1729 and 2162 Hz. Reproductive season of both species differed, autumn and winter for Uruguayan populations of P. bibroni and spring and summer for P. kriegi. Defensive encounter behavior (deimatic behavior) consisting in exhibition of the eye-like lumbar glands was documented in P. bibroni and P. kriegi (along with exposure of reddish flash coloration), and also in P. borellii, P. bufoninum and P. thaul. Similar behavior previously unreported for a Pleurodema species lacking noticeable lumbar glands was observed in P. tucumanum. The analysis of the literature, material in collections and fieldwork done by the authors over the last decade in Uruguay suggests that P. bibroni is undergoing severe decline. It was a common species up to the early 1970’s, but few populations close to each other in southeastern Uruguay are the only ones currently known. The conservation status of P. bibroni is of major concern as most known remnant populations are located in coastal areas with an increasing impact of urbanization. In contrast, P. kriegi seem to have stable populations, many of them within protected areas.